Process management: modern management approach (Research, Society and Development, 2023)
Business process management is important because effective business processes are crucial to a company's success. In this way, the present work aims to understand the Management of processes within the scope of Administration, thus aiming at business. Through a bibliographical review of a documental qualitative nature, in this way, the knowledge of other researchers will be used as a theoretical basis to expand the frontiers of knowledge through books, articles, periodicals and papers, and will develop current works. Business process management (BPM) is a structured approach to improving the processes that organizations use to get work done, serve their customers and drive business value. A business process is an activity or set of activities that helps achieve an organization's goals, such as increasing profits or promoting workforce diversity. The results reveal that the role of administrator is the role that a process manager assumes when controlling a process so that it works as planned. The main objective of the administrator role is to ensure that the plan is implemented without any deviations. It is important to note that BPM is not a specific automation technology. While it often involves automating many tasks, it is a mindset and methodology that allows people to streamline operations. This can happen with or without technology.